A hybrid characterization framework for structure-significant pulse-like features in ground motions. Issue 160 (September 2022) - Tang, Yuchuan; Wu, Chenhao; Wang, Jiankang
Abstract: In earthquake engineering and engineering seismology, it is fundamental to identify pulse-type ground motions and characterize their pulse-like features, as seismologists relate them to the fault rupture and engineers relate them to the structural response. Pulse-type ground motions have been observed to exhibit peculiar attributes both in the response spectrum and in the time series. The existing pulse identification methods rarely leverage the distinct feature in response spectrum sufficiently, and consequently only the mimicry in time series sometimes loses the impulsive effect of the original ground motion on the structures. Based on the self-similarity revealed by dimensional analysis, the current study developed a hybrid pulse characterization framework that starts from subregion-to-subregion similarity matching in response spectral space and finally achieves resemblance in time domain, for pulse-like features in either ground velocity or acceleration. The framework directly identifies the pulses that dominate the structural response. The framework is versatile in terms of allowing various pulse waveforms, switching among different types of response spectra, and coping with the ground motions that contain multiple structure-significant pulse-like features. Highlights: A versatile and extendable framework to identify and characterize pulse-like features in ground velocity or acceleration. Jointly leverage the peculiar attributes in both time domain and response spectral space for pulse characterization. Capable to characterize multiple pulse-like features in one ground motion that dominate structural responses. A highly efficient traversal algorithm to search for subregion-to-subregion similarity between two surfaces.